Magazine Executives See Bright Future; Communicatlon Responsibilities of the International Agricultural Research Centers; llustrations for Development: A Manual for Cross-Cultural Communication through Illustration and Workshops for Artists In Africa; A Q Study of Attitudes of Young Adults About Science and Science News - Myrna Daly; Paul Gwin; James W. King; Jim Shaner (Journal of Applied Communications, 1983)
Reviews of "Magazine Executives See Bright Future," in Folio: The Magazine for Management; "Communicatlon Responsibilities of the International Agricultural Research Centers," published by Agricultural Development Council, Inc., and the International Rice Research Institute; llustrations for Development: A Manual for Cross-Cultural Communication through Illustration and Workshops for Artists In Africa, edited by G. McBean, N. Kaggwa, and J. Bugembe; "A Q Study of Attitudes of Young Adults About Science and Science News," by Joye Patterson.